True.
Work is in attached sheet! <3
Answer:
Third option
Step-by-step explanation:
We can't factor this so we need to use the quadratic formula which states that when ax² + bx + c = 0, x = (-b ± √(b² - 4ac)) / 2a. However, we notice that b (which is 6) is even, so we can use the special quadratic formula which states that when ax² + bx + c = 0 and b is even, x = (-b' ± √(b'² - ac)) / a where b' = b / 2. In this case, a = 1, b' = 3 and c = 7 so:
x = (-3 ± √(3² - 1 * 7)) / 1 = -3 ± √2
The side length is the square root of 8. Because the square has 4 equal sides, the side lengths must be equal. So the answer is approximately 2.83.
Answer:
-3
Step-by-step explanation:
We know that both the larger triangle is dialated by some factor.
To start divide the two given sides:
36/24=1.5
This means that the larger triangle is dialated by a factor of 1.5, meaning that all sides of the smaller triangle must be multipled by 1.5 to get the larger triangle.
By knowing that we can multiply 3x-7 by 1.5 and set it equal to 6x-6.
1.5(3x-7)=6x-6
4.5x-10.5=6x-6
-6x+4.5x=10.5-6
-1.5x=4.5
x=(4.5)/(-1.5)
x= -3